Health Warnings: Reading Kazuo Ishiguro in Times of Crisis. Issue 7 (3rd October 2022) - Groes, Sebastian
ABSTRACT: This essay rereads Kazuo Ishiguro's depiction of the relationship between health, care and socio-economic inequality against the backdrop of our present time of crisis in which the COVID-19 pandemic features centrally. The pandemic has directly and indirectly laid bare and exacerbated various international crises and injustices that are shaping the structure of feeling of our times. Although Ishiguro's work does not (yet) address or represent the pandemic directly, the oeuvre is interesting for the ways it frames and responds to the many societal crises that characterise the early twenty-first century – and which the pandemic revealed and intensified. This essay explores specifically the ways in which Ishiguro's Never Let Me Go (2005) thinks about health, well-being and care in contemporary society, and how it depicts our own troubled empathetic relationship to institutions like the NHS and its workers. It will proceed to explore how Ishiguro's Klara and the Sun (2021) considers a new kind of crisis, namely, the interrelation of digital inequality and digital well-being, a problem the COVID-19 crisis intensified and accelerated. It concludes with an analysis of Ishiguro's call for a new social contract that is rooted in a new attitude towards others and the world that is open and dialogic.